2022
DOI: 10.1007/s10753-022-01660-x
|View full text |Cite
|
Sign up to set email alerts
|

The Integrated Analysis of Transcriptomics and Metabolomics Unveils the Therapeutical Effect of Asiatic Acid on Alcoholic Hepatitis in Rats

Abstract: The present study was to investigate the therapeutical effects and mechanisms of Asiatic acid from Potentilla Chinensis against alcoholic hepatitis. Rats were intragastrically fed with alcohol for 12 weeks to induce alcoholic hepatitis and then treated with various drugs for further 12 weeks. The results showed that Asiatic acid signi cantly alleviated liver injury caused by alcohol in rats, as evidenced by the improved histological changes and the lower levels of AST, ALT, and TBIL. Besides, Asiatic acid sign… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Cholestasis is closely related to metabolic disorders. Metabolomics can reveal the changes in the spectrum of endogenous metabolites in the body and further analyze the overall biological status and functional regulation of the body (S. Chen et al, 2022 ; Lin et al, 2020 ). After CR treatment, 45 metabolites in the serum were regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Cholestasis is closely related to metabolic disorders. Metabolomics can reveal the changes in the spectrum of endogenous metabolites in the body and further analyze the overall biological status and functional regulation of the body (S. Chen et al, 2022 ; Lin et al, 2020 ). After CR treatment, 45 metabolites in the serum were regulated.…”
Section: Discussionmentioning
confidence: 99%
“…However, high phosphatidylcholine levels were associated with a low risk of type 2 diabetes ( 20 ). The key metabolic pathway associated with these metabolites is glycerophospholipid metabolism, a type of lipid metabolism, and abnormal lipid metabolism is directly associated with oxidative stress and inflammatory responses ( 53 ). Compared to the T2DM-12w group, some LysoPC decreased in the T2DM-24w group, although the related mechanism needs to be explored further.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has a wide range of biological activities, such as anti-inflammatory, antioxidant, anti-infective, and anti-tumor effects [ 8 ]. Intensive studies in the past decades have revealed that AA plays a crucial role in myocardial injury [ [9] , [10] , [11] ], hepatitis [ 12 , 13 ], osteoporosis [ 14 , 15 ], tumors [ [16] , [17] , [18] , [19] ], bacterial and fungal infection [ 20 , 21 ], skin diseases [ 22 , 23 ], wound healing [ 24 ], and diabetes [ 25 , 26 ]. Furthermore, it has great potential in treating various neurological diseases such as spinal cord injury (SCI), neural tumors, traumatic brain injury (TBI), epilepsy, cerebral ischemia, Alzheimer's disease (AD), and Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%